The identity of twelve scincid generic names proposed by Cope in 1892 (Squamata: Scincidae) - Shea, Glenn M. (Zootaxa, 2021)
The twelve generic names proposed by Cope in 1892, which were created without included species, are linked to existing taxa by recognition that Cope’s key is a simple modification of the previous skink generic key by Boulenger in 1887, splitting existing genera of Boulenger in accordance with the morphology of the species included in those genera. This insight allows for Cope’s generic names Dicloniscus, Dimeropus, Haploscincus, Ollochirus, Oncopus, Podoclonium and Tridentulus to be linked to single species in Boulenger’s treatment, and thus those species are identified as the types of those genera, resulting in synonymy of Dicloniscus with Chalcides, Dimeropus with Larutia, Haploscincus with Lipinia, Podoclonium with Scelotes, and Ollochirus, Oncopus and Tridentulus with Lerista. Furcillus, Mesomycterus, Monophorus and Monophyaspis are associated with multiple species in Boulenger’s classification, and type species are designated that minimize change to existing nomenclature but facilitate application of the names to otherwise unnamed lineages in case future divisions are considered warranted. Furcillus becomes a synonym of Lerista, Mesomycterus becomes a synonym of Brachyseps, Monophorus becomes a synonym of Phoboscincus and Monophyaspis becomes a synonym of Trachylepis. Lepidothyrus, for which a type species was previously identified, is a synonym of Mochlus. Reversal of precedence is invoked to avoid the need for use of the senior synonyms Dimeropus and Monophorus over the frequently used Larutia and Phoboscincus, however, Mesomycterus is a senior synonym of Brachyseps, and replaces that recently created name.